UJI AKTIVITAS PENURUNAN KOLESTEROL PRODUK MADU HERBAL YANG BEREDAR DI PASARAN PADA TIKUS PUTIH DIET LEMAK TINGGI - Ni Putu Ariantari; Sagung Chandra Yowani; Dewa Ayu Swastini (Jurnal Kimia (Journal of Chemistry), 2010)
The research aims to investigate hypocholesterolemic activity of two marketed herbal honey products forhypocholesterolemia, mentioned as product A and B on Wistar albino rats with hypercholesterolemic diet.Hypocholesterolemic activity test was conducted with Enzymatic Photometric Test CHOD-PAP (CholesterolOxidase Phenol Aminoantipyrin) method. The result revealed that product A administered orally to Wistar albino ratswith hypercholesterolemic diet, at 0.15 mL/200g BW dose once daily, did not show hypocholesterolemic activity. Onthe other hand, product B at 0.5 mL/200g BW dose showed hypocholesterolemic activity similar to simvastatin.